LIFESTYLE ENGINEERING DURING THE FIRST CENTURIES OF THE COMMON ERA - Carina Prestes (Centro Universitário Adventista de São Paulo, 2022)
The three capital cities of the Levant had just gone through major constructions and/or renovations during Jesus's ministry. These new or renovated cities-Tiberias, Caesarea Philippi, and Jerusalem-were their rulers' display of power and wealth. This article analyzes these capital cities in Palestine during Jesus's ministry and suggests some implications of such constructions for the worldview of their citizens and for the spread of Christianity.